Upaya Meningkatkan Karakter IMTAK Peserta Didik Melalui Pembiasaan Shalat Berjamaah dan Tilawah Al-Qur’an di SMPN 2 Satu Atap Jambon - Puput Saputra (BASICA, 2023)
This written research aims to examine Efforts to Improve Students' Imtaq Character Through the Habit of Congregational Prayer and Al-Qur'an Recitation at SMPN 2 Satu Atap Jambon. This written research aims to examine how teachers' efforts are made to improve students' IMTAQ character, how to implement the habit of congregational prayer, how to get used to Al-Qur'an recitation, and how to implement the habit of congregational prayer and Al-Qur'an recitation in improving students' IMTAQ character at SMPN 2 Satu Atap Jambon. The research method used in this study is qualitative research with a descriptive approach. Data were obtained through interview, observation, and documentation methods. Then the data analysis technique uses the data reduction method, data presentation, and drawing conclusions. The results of the study showed that the efforts of teachers in improving the IMTAQ character of students at SMPN 2 Satu Atap Jambon were divided into 2 main activities, namely the habit of congregational prayer and recitation of the Qur'an. The implementation of the habit of congregational prayer is carried out every day by teachers and students, including the habit of recitation of the Qur'an which is also carried out every day so that students are able to understand and practice the Qur'an properly and correctly. The implementation of the habit of congregational prayer and recitation of the Qur'an has been able to improve the IMTAQ character of students, as evidenced by changes in character both at school and at home. One of them is that students are able to carry out worship diligently, complete every school assignment completely, and obey every school regulation and regulation at home. Students who participate in the habit of congregational prayer and recitation of the Qur'an are also able to interpret and apply the character of faith and piety as the foundation of Islam even though they are in public schools. In this way, students have the provisions to face the next life through the habit of praying in congregation and reciting the Qur'an